2021
DOI: 10.1002/ijc.33753
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of duodenal cancer by upper gastrointestinal‐endoscopy in Lynch syndrome

Abstract: Small bowel cancer (SBC) is the malignancy with the highest standardized incidence ratio in Lynch syndrome (LS) patients. Of all SBCs, about 50% are duodenal cancers (DCs), therefore being accessible by esophago-gastro-duodenoscopy (EGD) for surveillance. We asked whether early detection of DC is possible for LS patients undergoing surveillance by EGD and if surveillance should be limited to specific subgroups.Data for LS patients with DC were retrieved from the registry of the German Consortium for Familial I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It is known that colorectal and gynecologic-related cancers often develop at earlier ages in Lynch syndrome compared to the general population [ 7 , 70 ], and data confirm this in UGI cancers as well [ 49 , 54 , 65 ]. Therefore, we advocate for early initiation of UGI surveillance in Lynch syndrome beginning at age 30, or 2–5 years before the youngest UGI cancer in the family, whichever is earliest ( Figure 2 ).…”
Section: Ugi Surveillance Implementation and Controversiesmentioning
confidence: 94%
See 1 more Smart Citation
“…It is known that colorectal and gynecologic-related cancers often develop at earlier ages in Lynch syndrome compared to the general population [ 7 , 70 ], and data confirm this in UGI cancers as well [ 49 , 54 , 65 ]. Therefore, we advocate for early initiation of UGI surveillance in Lynch syndrome beginning at age 30, or 2–5 years before the youngest UGI cancer in the family, whichever is earliest ( Figure 2 ).…”
Section: Ugi Surveillance Implementation and Controversiesmentioning
confidence: 94%
“…A recent German study evaluating the detection of duodenal cancer in Lynch syndrome identified 49 duodenal cancers in 47 patients, with the majority (91%) of patients having a MLH1 or MSH2 pathogenic variant [ 65 ]. While the median age at diagnosis of duodenal cancer was 51.7 years, 10% of patients were less than 35 years old at the time of diagnosis.…”
Section: Duodenal Cancermentioning
confidence: 99%
“…(Table 1) Two studies comparing surveillance and nonsurveillance-based diagnostic EGDs reported that over two-thirds of UGI cancers identified on screening EGD were stage I while less than one-third of UGI cancers found on diagnostic EGDs were stage I 6,9. Although the results of these recent studies support EGD surveillance, study limitations include heterogeneity in study design, lack of systematic data reporting, a short length of follow-up, and no quality standards for EGD performance in LS 5–10…”
Section: Introductionmentioning
confidence: 99%
“…The majority (50% to 80%) of small bowel cancers in LS are reported to occur in the duodenum 46–48. Adenomas are the presumed precursor lesion for duodenal adenocarcinoma and have been reported in up to 2.8% of patients with LS; thus, identification and resection of these lesions are vital 4–8,10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation